Luther: A Mystic. Issue 2 (June 2017) - Leppin, Volker
Abstract: Understanding Martin Luther means looking at a medieval monk heavily influenced by his confessor, John of Staupitz. Staupitz inspired Luther and his friends to read the sermons of the late medieval mystic John Tauler. Here Luther found a theology of grace, the idea that faith is the only remaining point to a grace‐full God. Tauler's most obvious influence, his understanding of penance, shaped the first and second of Luther's Ninety‐five Theses . Another influence, that of passion mysticism, Luther explored and developed in his early tracts. Over the years, while Luther would stress the importance of Scripture over mystical experience, this was more a slight but meaningful transformation rather than a complete break with mysticism.